Multiphase dolomitization mechanisms of the Cambrian upper Changping Formation, North China Platform, China - Bai, Ying; Zhao, Zhenyu; Zhao, Zhe; Gao, Jianrong (Frontiers in Earth Science, 2023)
The Cambrian dolomite reservoirs of the North China Platform offer good exploration prospects, but their occurrence and the impacts of dolomitization on reservoir quality are not yet clearly understood. The study herein assessed outcrop samples in the Cambrian upper Changping Formation, Dingjiatan area. A combination of petrology, fluid inclusion microthermometry, isotopes, and trace element compositions was used to explain multiphase dolomitization mechanisms and their impacts on dolomite reservoirs. Five types of dolomites were identified through outcrop observations, thin section identification via transmitted light, and cathodoluminescence (CL). The following geochemical analysis revealed various dolomitization mechanisms. In the (pene)contemporaneous stage, microbial dolomite (mD) was self-microbial with significant carbon isotopic depletion compared to the Cambrian seawater values. With the influence of microbial dolomitization, dolomicrite (DM) corresponded to the sabkha dolomitization mode in a low-salinity seawater environment and early-stage dolomitization. The structureless dolomite (ssD) in the early highstand systems tract (EHST), characterized by elevated 87Sr/88Sr ratios and low oxygen isotopic values, formed from stratum brine water in the shallow-middle burial stage rather than in the (pene)contemporaneous stage. In contrast, ssD in the late highstand systems tract (LHST) underwent (pene)contemporaneous dolomitization at salinities between 6% and 28% before later pore water transformation, with the participation of atmospheric freshwater through faults and unconformities exhibiting the lowest inclusion temperature and salinity values. The medium to coarse crystalline dolomite (MCD) in the LHST and the saddle dolomite (SD) in the EHST with low REE values were atypical hydrothermal dolomites caused by a combined superposition of middle-deep burial hydrothermal fluids at temperatures > 150℃ and stratigraphic brines. The MCD was also influenced by terrigenous water characterized by relatively low Eu anomaly values. Finally, the mechanisms of porosity increase were investigated, and it was concluded that the pore increase caused by the (pene)contemporaneous reflux interaction and the later pore retention led to better ssD reservoirs in the LHST than in the EHST.